Investigating the Appropriateness of Admission and Hospitalization at a Teaching Hospital: A Case of a Developing Country - Mahmood NEKOEI MOGHADAM; Mohammadreza AMIRESMAILI; Reza GOUDARZI; Saeed AMINI; Sajad KHOSRAVI (Iranian Journal of Public Health, 2017)
Background: Reduction of inappropriate use of health services can decrease health care costs without harming the quality of services. This study aimed to investigate inappropriate admission and hospitalization at Afzalipour Hospital of Kerman, Iran.